2022
DOI: 10.3390/nu14142852
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Reduces Social Isolation and Anxiety in Adult Female Nonhuman Primates

Abstract: Dietary composition is associated with the differential prevalence of psychiatric disorders; the Western diet confers increased risk, while the Mediterranean diet appears to reduce risk. In nonhuman primates, anxiety-like behaviors and social isolation have been linked to both Western diet consumption and increased inflammatory disease risk, and recent evidence suggests that diet composition may affect immune system function in part through its effects on behavior. This is particularly important in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…Previously we showed that the indices of peripheral inflammation in this study were associated with social isolation and anxiety, behaviors thought to be associated with neuroinflammation [42]. Here we show that brain CDK14 transcript levels were positively associated with anxiety behavior and time spent alone consistent with previous associations of Western diet consumption with increased risk of anxiety [6].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previously we showed that the indices of peripheral inflammation in this study were associated with social isolation and anxiety, behaviors thought to be associated with neuroinflammation [42]. Here we show that brain CDK14 transcript levels were positively associated with anxiety behavior and time spent alone consistent with previous associations of Western diet consumption with increased risk of anxiety [6].…”
Section: Discussionsupporting
confidence: 90%
“…The behavioral characterization of these animals has been described in-depth [51]. Briefly, behavioral data were collected weekly during two 10-min focal observations [52], balanced for the time of day for 24 consecutive months beginning the third month of the treatment phase (approximately 200 behavior samples/monkey, mean = 31.0 h/monkey, and 1178 observation hours total).…”
Section: Social Isolation and Anxiety Behavior Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The now classic research above illustrates that the evidence for the role of nutrition in anxiety, depression, and associated behavior is long term, broad and deep. In this Special Issue, Johnson, Shively, and colleagues used non-human primates to achieve the kind of experimental control of dietary conditions that allows clarification of causal statements regarding the effect of nutrition on behavior [ 2 ]. The introduction of an unhealthy diet caused a rapid decline in normal behaviors and an increase in anxiety-like behaviors.…”
Section: History Of Nutrition and Behavior Researchmentioning
confidence: 99%
“…11 Studies conducted on non-human primates have shown that the Western diet can increase anxiety-like behaviors, while the Mediterranean diet can reduce this risk. 12 Fat intake has been found to have a positive association with cognitive impairment, mood disorders, and anxiety, and it also affects neuropsychiatric function. 13 The microbiota related to a high-fat diet increased anxiety and stereotypical behaviors and reduced memory in mice.…”
Section: Introductionmentioning
confidence: 99%